Child and women domestic abuse victims' social health insurance protection: an affirmative justice perspective - Sasono, Satryo; Isharyanto, Isharyanto; Putri, Delasari Krisda (Journal of Law, Environmental and Justice, 2023)
As the times develop, the more complex the problems faced, one of which is problems related to the family, namely domestic violence (KDRT). The emergence of violence results in victims who must be protected, both physically and psychologically. The protection provided to victims of domestic violence is legal protection and health protection. Health social security for victims is an important factor needed by victims of violence, legal protection for victims is no less important considering that until now there are still not many victims who report acts of domestic violence that have befallen them. Based on the description above, it becomes an interesting problem which is outlined in the formulation of the problem as follows: 1) Cases of violence and influencing factors; 2) Principles of health insurance protection for victims of domestic violence; 3) Legal protection efforts for children and women as victims of domestic violence. Thus, the focus of this research is how the urgency of regulation on the protection of victims of criminal acts in obtaining social health insurance. This research is a normative-empirical legal research (applied law research) that uses case studies in the form of legal behavior products. This research is a normative legal research that is perspective analysis with a statutory approach. The result of this research is the importance of social health insurance and legal protection for victims of domestic violence.